Über den Zusammenhang von Versstruktur, Strophenform und rhythmischer Gestalt der Genfer Psalmlieder - Aeschbacher, Gerhard (Jahrbuch für Liturgik und Hymnologie, 1987)
The starting point of this study is the well known controversy how to explain and to reproduce the rests at the end of the lines in the psalter of Geneva. A principal mensural understanding does not match the tunes in the psalmody of Geneva (although this way of performance became soon very common in french speaking countries); these tunes cannot be taken for mensural music in the sence of the 16th century. This mensural music shows a continous formation by tactus-units which do not occur within the tunes of Geneva at all. Their rhythmical form seems to be derived from the principles of the french verse, from its accent fixe at the end and partially in the middle of each line and from the breaks belonging to each line. The coherence of words and tune or tune-rhythm strongly depends on formal aspects as for instance on the structure of the whole verse. Translated into German this coherence and the breaks change their function which means that a general formal rule concerning the musical reproduction of these rests cannot be given.